Emerging Strategies for Mitigating Acid Mine Drainage Formation and Environmental Impacts: A Comprehensive Review of Recent Advances - Yudha Gusti Wibowo; Muhammad Fauzul Imron; Setyo Budi Kurniawan; Bimastyaji Surya Ramadan; Tarmizi Taher; Alvian Hayu Sudibya; Hutwan Syarifuddin; Khairurrijal Khairurrijal; Jarwinda (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2023)
Acid mine drainage (AMD) is a significant threat to the environment due to its high acidity and metal ion content. To effectively eliminate pollutants from AMD, various approaches are necessary. This review aims to provide a comprehensive understanding of recent advances in AMD mitigation. While treatment technologies have developed to eliminate AMD, they often produce sludge as a by-product and require expensive maintenance. As a cost-effective alternative, the recovery of AMD resources can reduce toxicity and promote reuse of heavy metals and rare earth elements. This review also analyzes the challenges and prospects of AMD mitigation implementation, including current mitigation conditions and knowledge gaps. Researchers can benefit from this review by gaining insight into research progress in this area, identifying strengths and weaknesses of current AMD mitigation applications, and exploring future research directions.